(untitled) (Research, Society and Development, 2020)
Despite being less notified, psychological abuse of teachers against existing students and brings serious harm to the victim. Considering the lack of studies and the recognition of the quality of instruments that aim at verifying and assessing a given phenomenon, this study aimed to develop the Psychological Violence Against University Students Scale (EVIPSI) which measures violent behaviors displayed by teachers against university students. This study adopted the Pasquali methodological reference model based on three procedures (theoretical, empirical, and analytical). The final version of the scale was organized into 28 items, divided into two dimensions: hostile actions from the teacher (s) to the student; and student stress in relation to the teacher (s). The process of content validation occurred during the theoretical procedure, in association with other types of validation to comply with the empirical and analytical procedures and achieve an effective validation.